2004
DOI: 10.1002/jip.12
|View full text |Cite
|
Sign up to set email alerts
|

Commuters and marauders: an examination of the spatial behaviour of serial criminals

Abstract: The demographic characteristics of serial offenders that distinguish between the commuter and the marauder offence styles were examined. Proposed by Canter and Larkin (1993)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 13 publications
(34 reference statements)
5
28
0
3
Order By: Relevance
“…The importance of the offender's home was also revealed in an examination of serial murderers' disposal-site location choice (Lundrigan & Canter, 2001a,b). Meaney (2004) not only found similar fi ndings but also demonstrates that the offence venue choice models are related to the type of crime. More specifi cally, she found that the marauder model was more likely to be adopted by sex offenders located in a metropolitan area, whereas the commuter model was more typical for adult male burglars.…”
supporting
confidence: 58%
“…The importance of the offender's home was also revealed in an examination of serial murderers' disposal-site location choice (Lundrigan & Canter, 2001a,b). Meaney (2004) not only found similar fi ndings but also demonstrates that the offence venue choice models are related to the type of crime. More specifi cally, she found that the marauder model was more likely to be adopted by sex offenders located in a metropolitan area, whereas the commuter model was more typical for adult male burglars.…”
supporting
confidence: 58%
“…Patterns of mobile offenders have been observed and are often taken along in differentiated offender typologies. Herein, perpetrators offending in a circle around their homes are called marauders, whereas those travelling to other regions are referred to as commuters (Canter & Larkin, 1993;Kocsis, Cooksey, Irwin, & Allen, 2002;Meaney, 2004;Paulsen, 2007). Yet, mobile offenders too have incentives to leave known territory (Van Koppen & Jansen, 1998, p. 231).…”
Section: Travelling Criminalsmentioning
confidence: 99%
“…Meaney (2004) investigated the infl uence of demographic characteristics (age, gender, ethnicity), crime type (arson, rape, burglary), and environment type (rural or urban) on offender spatial patterns and found that the two groups could be differentiated on certain offender, offence, and environmental features. The proposal that explanations for different spatial patterns may lie partly in the environmental features of offending makes the assumption that such variables are stable or consistent enough across a series to be meaningfully utilised to distinguish between spatial patterns.…”
Section: Spatial Differentiationmentioning
confidence: 99%